A study on customer perception of Banting - Klang, Route 127 of kenderaan Klang Banting Berhad / Rafkah Asri - Asri, Rafkah (1999)
Transportation system in the world today has influenced the demand pattem. These occur because demand for transport is indirect. When this happen, the transport operators are important to play their role and fulfil the customers needs. Currently, transportation system today needs an excellent strategy in order to achieve the company's objective.